Coexistence of PFAPA syndrome with separation anxiety - Yunus Emre Donmez; Ozlem Ozcan; Yilmaz Tabel (Medicine Science, 2019)
PFAPA syndrome is an auto inflammatory disease. Researchers have stated that auto inflammatory mechanisms can play a role in etiology of several psychiatric diseases and for this reason auto inflammatory diseases are frequently associated with psychiatric disorders. The purpose of this paper, it is aimed to report two cases diagnosed with PFAPA syndrome and having psychiatric symptoms and to discuss them accompanied by literature data. As authors, in the light of cases we report and literature knowledge, we think that children with PFAPA syndrome could be under risk in terms of psychiatric problems due to common inflammatory etiology. [Med-Science 2019; 8(1.000): 247-9]